Tinjauan Yuridis Perbuatan Melanggar Hukum (PMH) Penyalahgunaan Data Pribadi Aplikasi di Google Play Store - Anisa Isti Briliany; Anajeng Esri Edhi Mahanani (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2022)
The industrial revolution 4.0 in Indonesia can be seen by the massive use of the internet in people's daily activities through electronic systems in the form of websites and applications for searching information, socializing and commercial activities. Access of applications become easier by installing on personal gadgets such as smartphones that are supported by one of the best known operating systems, which is Android with Google Play Store as digital application service provider. However, behind all the conveniences some applications demand a lot of user personal data such as detailed user financial information to continue transactions. It has the risk of violating the law that injures the rights of others due to violating laws and regulations, or violating the interests of others as specified in Article 1365 of the Civil Code. Through this research, it can be identified that there are forms of unlawful acts that occur for the misuse of personal data, namely vulnerabilities in data security, lack of transparency over the fate of data through notifications, and administrative defects in providing applications. The three types of unlawful acts are reviewed based on the applicable regulations including Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions, Government Regulation Number 71 of 2019 concerning System Operations and Electronic Transactions, and Google Play Store regulations in the form of program developer policies and developer distribution agreements, in hope that a dispute resolution can finally be found either through litigation or non-litigation. Keywords : unlawful act, transparency, personal data